Motivation as a mechanism underpinning exercise-based falls prevention programmes for older adults with cognitive impairment: a realist review. Issue 6 (19th June 2019) - Booth, Vicky; Harwood, Rowan; Hancox, Jennie E; Hood-Moore, Victoria; Masud, Tahir; Logan, Phillipa
Abstract : Objectives: This review aimed to identify mechanisms underlying participation in falls prevention interventions, in older adults with cognitive impairment. In particular we studied the role of motivation. Design: A realist review of the literature. Data sources: EMBASE, MEDLINE, CINAHL, the Cochrane Library, PsycINFO and PEDRO. Eligibility criteria: Publications reporting exercise-based interventions for people with cognitive impairment, including dementia, living in the community. Data extraction and synthesis: A 'rough programme theory' (a preliminary model of how an intervention works) was developed, tested against findings from the published literature and refined. Data were collected according to elements of the programme theory and not isolated to outcomes. Motivation emerged as a key element, and was prioritised for further study. Results: An individual will access mechanisms to support participation when they think that exercise will be beneficial to them. Supportive mechanisms include having a 'gate-keeper', such as a carer or therapist, who shares responsibility for the perception of exercise as beneficial. Lack of access to support decreases adherence and participation in exercise. Motivational mechanisms were particularly relevant for older adults with mild-to-moderate dementia, where the exercise intervention was multicomponent, in a preferred setting, at the correct intensity and level of progression, correctly supported and considered, and flexibly delivered. Conclusion: Motivation is a key element enabling participation in exercise-based interventions for people with cognitive impairment. Many of the mechanisms identified in this review have parallels in motivational theory. Clinically relevant recommendations were derived and will be used to further develop and test a motivationally considered exercise-based falls intervention for people with mild dementia. PROSPERO registration number: CRD42015030169.